Acute massive pulmonary embolism: Clinical and haemodynamic findings in 23 patients studied by cardiac catheterization and pulmonary arteriography - Miller, G. A. H. (1970)
Twenty-three patients are reported in whom a diagnosis of acute massive pulmonary embolism was confirmed by pulmonary arteriography. All patients had a history of less than 48 hours' duration and only two had previous cardiorespiratory disease. In such patients the haemodynamic abnormalities determined at catheterization are due to pulmonary embolism as an isolated disturbance. These abnormalities include an only moderate degree of pulmonary hypertension (PA systolic pressure 38.4±6.8 mm. Hg), right ventricular `failure' (RVED 11.5±4.9 mm. Hg), arterial oxygen desaturation (86.4±11.2%) and a wide arteriovenous oxygen difference (8.1±1.8 ml./100 ml.), and low cardiac output. These haemodynamic abnormalities find their expression in the presentation and the clinical, electrocardiographic, and radiological findings which are described.